Redução do efeito do multicaminho de freqüências alta e baixa no posicionamento relativo cinemático utilizando wavelets: Resultados preliminares - de Souza, Eniuce Menezes [UNESP]; Monico, João Francisco Galera [UNESP]; Pagamisse, Aylton [UNESP] (My University, 2009)
Multipath reduction from GPS signal has become essential for any highly precise applications. The high-frequency multipath from far surfaces, which causes the smaller errors, is easier to be mitigated. But the low-frequency multipath from near surfaces, which causes the major errors, is very difficult to be reduced or modeled, mainly in kinematic applications. A possible multipath reduction that has showed promising performance in static relative positioning is the Multiresolution Analysis (MRA) using wavelets. Thus, the aim of this paper is to investigate the possibility of extending this wavelet method to reduce multipath effects for kinematic applications. An experiment was carried out using objects placed close to the receiver antenna to cause, mainly, low-frequency multipath. The multipath effects impeded the reliable ambiguity resolution during the processed data period. With the multipath mitigation using the proposed method based on wavelets, ambiguities could be fixed with reliably in beginning of the processing and the coordinates became much more accurate. It was obtained up to 1.29 m of improvement on the resulting coordinates.
Multipath reduction effect of the high and low frequency in static relative positioning by using wavelets: Preliminary results
Keywords: Ambiguities; Gps kinematic positioning; Multipath; Wavelet